Geothermal energy: an opportunity of dialogue in pursuit of sustainable development in Peru - Cruz Pauccara, Vicentina (2015)
9 páginas. | Trabajo presentado en el World Geothermal Congress 2015, Melbourne, Australia, 19-25 abril, 2015.